Variasi Morfologi Burung Perkutut Berdasarkan Ras dan Warna Bulu yang Diternakkan di Daerah Istimewa Yogyakarta - Bambang Agus Suripto; Celine Christina; Ilmia Rosame (Biotropic : The Journal of Tropical Biology, 2022)
The zebra dove (Geopelia striata) has been a long-time favorite of many people for bird-keeping and birdsong competition which are common pastimes in Southeast Asia. The diversity of zebra doves below the species level still needs to be investigated in terms of breeding, projecting the development of internal or external bird-keeping markets, and conservation for populations in the wild as potential damage-control of the captured bird market. This study aimed to study the morphologically significant differences between the main groups of zebra doves (Local, Bangkok, Cemani Majapahit, Cemani, and Golden) and certain coat colors (silver, mocca, white striated, white cotton, cream, and black) which are traded in Special Region of Yogyakarta. The research was divided into two stages, namely surveys to breeders and hobbyists and morphometric and qualitative data collection, namely color. The results of the morphometric measurements of each individual were then grouped using SPSS Statistics and the Unweighted Pair Group Method with Arithmetic (UPGMA) method to determine whether the variables tested are significantly different. To see the clustering and distribution of the tested variables, Principal Component Analysis was performed. The results obtained show the amount of overlap in the scree plot, this proves that there is no significant difference between the race and color variants of zebra doves grouped by traders in the Special Region of Yogyakarta.